Estimating wastewater dilution using chemical markers and incomplete flow measurements: Application to normalisation of SARS-CoV-2 measurements - Owen D. Jones; Amy J. Baldwin; Isabelle Durance; William B. Perry; Andrew Weightman (Journal of Water Process Engineering, 2026)

Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

Reproductive risk of Neonicotinoids: A review of male rodent studies - Sumaiya S. Irfan; Veronica G. Sanchez; Michael S. Bloom; Helen B. Chin; Virginia Espina; Jenna R. Krall; Anna Z. Pollack; Lance A. Liotta; Melissa J. Perry (Environmental Research, 2025)

Genome-resolved metagenomics uncovers antimicrobial resistance gene carriers in hospital and municipal wastewater environments - Reshma Silvester; Gordon Webster; William B. Perry; Kata Farkas; Laura Rushton; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; Davey L. Jones (Science of The Total Environment, 2025)

Comment on “Tianeptine Exposures Reported to United States Poison Centers, 2015–2023” - James B. Leonard; Perry E. Rosen; Christopher J. Counts (Journal of Medical Toxicology, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Metagenomics unveils the role of hospitals and wastewater treatment plants on the environmental burden of antibiotic resistance genes and opportunistic pathogens - Reshma Silvester; William B. Perry; Gordon Webster; Laura Rushton; Amy Baldwin; Daniel A. Pass; Nathaniel Healey; Kata Farkas; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; et al. (Science of The Total Environment, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Producing 3D radargrams from orbital radar sounding data at Mars: History, results, methods, lessons and plans - Frederick J. Foss; Nathaniel E. Putzig; Bruce A. Campbell; Stewart A. Levin; Matthew R. Perry; John W. Holt; Michael S. Christoffersen; Isaac B. Smith; Gareth A. Morgan; Aaron T. Russell (Icarus, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Examining the stability of viral RNA and DNA in wastewater: Effects of storage time, temperature, and freeze-thaw cycles - Rachel C. Williams; William B. Perry; Kathryn Lambert-Slosarska; Ben Futcher; Cameron Pellett; India Richardson-O'Neill; Steve Paterson; Jasmine M.S. Grimsley; Matthew J. Wade; Andrew J. Weightman; Kata Farkas; Davey L. Jones (Water Research, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Retrieving canopy nitrogen concentration and aboveground biomass with deep learning for ryegrass and barley: Comparing models and determining waveband contribution - Manish Kumar Patel; José Padarian; Andrew W. Western; Glenn J. Fitzgerald; Alex B. McBratney; Eileen M. Perry; Helen Suter; Dongryeol Ryu (Field Crops Research, 2023)

Influence of corn supplementation to beef cows during mid- to late-gestation: Supplementation decreases placental microvascular surface density but does not alter uterine blood flow or neonatal performance1 - A.R. Tanner; M.L. Bauer; K.C. Swanson; V.C. Kennedy; J.D. Kirsch; J. Gaspers; N. Negrin-Pereira; A.B.P. Fontoura; G.A. Perry; G. Stokka; A. Rodas-Gonzalez; A. Ward; et al. (Livestock Science, 2023)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recursive Bayesian computation facilitates adaptive optimal design in ecological studies - Clinton B. Leach; Perry J. Williams; Joseph M. Eisaguirre; Jamie N. Womble; Michael R. Bower; Mevin B. Hooten (Ecology, 2022)
Optimal design procedures provide a framework to leverage the learning generated by ecological models to flexibly and efficiently deploy future monitoring efforts. At the same time, Bayesian hierarchical models have become widespread in ecology and offer a rich set of tools for ecological learning and inference. However, coupling these methods with an optimal design framework can become computationally intractable. Recursive Bayesian computation offers a way to substantially reduce this computational burden, making optimal design accessible for modern Bayesian ecological models. We demonstrate the application of so‐called prior‐proposal recursive Bayes to optimal design using a simulated data binary regression and the real‐world example of monitoring and modeling sea otters in Glacier Bay, Alaska. These examples highlight the computational gains offered by recursive Bayesian methods and the tighter fusion of monitoring and science that those computational gains enable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Matrix-level co-occurrence metrics are sensitive to sampling grain: a case study in species-rich shrublands - G. L. W. Perry; Ben P. Miller; Byron B. Lamont; Neal J. Enright (Plant Ecology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Correction to: “Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta” - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2020)

Coral Reefs of Abu Dhabi, United Arab Emirates: Analysis of Management Approaches in Light of International Best Practices and a Changing Climate - Haïfa Ben-Romdhane; Rima W. Jabado; Edwin Mark Grandcourt; Richard John Obrien Perry; Ayesha Yousef Al Blooshi; Prashanth Reddy Marpu; Taha B. M. J. Ouarda; Hosni Ghedira (Frontiers in Marine Science, 2020)

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Temporal relationship between the Lassen volcanic center and mafic regional volcanism - Aurelie Germa; Chris Perry; Xavier Quidelleur; Andrew Calvert; Michael Clynne; Charles B. Connor; Laura J. Connor; Rocco Malservisi; Sylvain Charbonnier (Bulletin of Volcanology, 2019)

Developing a Social–Ecological–Environmental System Framework to Address Climate Change Impacts in the North Pacific - Steven J. Bograd; Sukyung Kang; Emanuele Di Lorenzo; Toyomitsu Horii; Oleg N. Katugin; Jackie R. King; Vyacheslav B. Lobanov; Mitsutaku Makino; Guangshui Na; R. Ian Perry; Fangli Qiao; Ryan R. Rykaczewski; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Arbuscular mycorrhizal fungi associated with Leptospermum scoparium (mānuka): effects on plant growth and essential oil content - Wisnu Adi Wicaksono; Catherine E. Sansom; E. Eirian Jones; Nigel B. Perry; Jana Monk; Hayley J. Ridgway (Symbiosis, 2018)

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Monitoring dynamic spatio‐temporal ecological processes optimally - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower (Ecology, 2018)
Population dynamics vary in space and time. Survey designs that ignore these dynamics may be inefficient and fail to capture essential spatio‐temporal variability of a process. Alternatively, dynamic survey designs explicitly incorporate knowledge of ecological processes, the associated uncertainty in those processes, and can be optimized with respect to monitoring objectives. We describe a cohesive framework for monitoring a spreading population that explicitly links animal movement models with survey design and monitoring objectives. We apply the framework to develop an optimal survey design for sea otters in Glacier Bay. Sea otters were first detected in Glacier Bay in 1988 and have since increased in both abundance and distribution; abundance estimates increased from 5 otters to >5,000 otters, and they have spread faster than 2.7 km/yr. By explicitly linking animal movement models and survey design, we are able to reduce uncertainty associated with forecasting occupancy, abundance, and distribution compared to other potential random designs. The framework we describe is general, and we outline steps to applying it to novel systems and taxa.

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Genome-wide detection of genetic loci associated with soybean aphid resistance in soybean germplasm PI 603712 - Siddhi J. Bhusal; Guo-Liang Jiang; Qijian Song; Perry B. Cregan; David Wright; Jose L. Gonzalez-Hernandez (Euphytica, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Warming and provenance limit tree recruitment across and beyond the elevation range of subalpine forest - Lara M. Kueppers; Erin Conlisk; Cristina Castanha; Andrew B. Moyes; Matthew J. Germino; Perry de Valpine; Margaret S. Torn; Jeffry B. Mitton (Global Change Biology, 2017)
Climate niche models project that subalpine forest ranges will extend upslope with climate warming. These projections assume that the climate suitable for adult trees will be adequate for forest regeneration, ignoring climate requirements for seedling recruitment, a potential demographic bottleneck. Moreover, local genetic adaptation is expected to facilitate range expansion, with tree populations at the upper forest edge providing the seed best adapted to the alpine. Here, we test these expectations using a novel combination of common gardens, seeded with two widely distributed subalpine conifers, and climate manipulations replicated at three elevations. Infrared heaters raised temperatures in heated plots, but raised temperatures more in the forest than at or above treeline because strong winds at high elevation reduced heating efficiency. Watering increased season‐average soil moisture similarly across sites. Contrary to expectations, warming reduced Engelmann spruce recruitment at and above treeline, as well as in the forest. Warming reduced limber pine first‐year recruitment in the forest, but had no net effect on fourth‐year recruitment at any site. Watering during the snow‐free season alleviated some negative effects of warming, indicating that warming exacerbated water limitations. Contrary to expectations of local adaptation, low‐elevation seeds of both species initially recruited more strongly than high‐elevation seeds across the elevation gradient, although the low‐provenance advantage diminished by the fourth year for Engelmann spruce, likely due to small sample sizes. High‐ and low‐elevation provenances responded similarly to warming across sites for Engelmann spruce, but differently for limber pine. In the context of increasing tree mortality, lower recruitment at all elevations with warming, combined with lower quality, high‐provenance seed being most available for colonizing the alpine, portends range contraction for Engelmann spruce. The lower sensitivity of limber pine to warming indicates a potential for this species to become more important in subalpine forest communities in the coming centuries.

Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2017)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

An integrated data model to estimate spatiotemporal occupancy, abundance, and colonization dynamics - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower; Trevor J. Hefley (Ecology, 2017)
Ecological invasions and colonizations occur dynamically through space and time. Estimating the distribution and abundance of colonizing species is critical for efficient management or conservation. We describe a statistical framework for simultaneously estimating spatiotemporal occupancy and abundance dynamics of a colonizing species. Our method accounts for several issues that are common when modeling spatiotemporal ecological data including multiple levels of detection probability, multiple data sources, and computational limitations that occur when making fine‐scale inference over a large spatiotemporal domain. We apply the model to estimate the colonization dynamics of sea otters ( Enhydra lutris ) in Glacier Bay, in southeastern Alaska.

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Identification and evaluation of quantitative trait loci underlying resistance to multiple HG types of soybean cyst nematode in soybean PI 437655 - Yongqing Jiao; Tri D. Vuong; Yan Liu; Clinton Meinhardt; Yang Liu; Trupti Joshi; Perry B. Cregan; Dong Xu; J. Grover Shannon; Henry T. Nguyen (Theoretical and Applied Genetics, 2015)

Relationships between aerosols and precipitation in the southern Appalachian Mountains - G. M. Kelly; B. F. Taubman; L. B. Perry; J. P. Sherman; P. T. Soulé; P. J. Sheridan (International Journal of Climatology, 2013)
There are many uncertainties associated with aerosol‐precipitation interactions, particularly in mountain regions where a variety of processes at different spatial scales influence precipitation patterns. Statistical relationships between aerosols and precipitation were examined in the southern Appalachian Mountains to determine the seasonal and synoptic influences on these relationships, as well as the influence of air mass source region. Precipitation events were identified based on regional precipitation data and classified using a synoptic classification scheme developed for this study and published in a separate manuscript (Kelly et al . 2012). Hourly aerosol data were collected at the Appalachian Atmospheric Interdisciplinary Research ( AppalAIR ) facility at Appalachian State University in Boone, NC (1110 m asl, 36.215°, –81.680°). Backward air trajectories provided information on upstream atmospheric characteristics and source regions. During the warm season (June–September), greater aerosol loading dominated by larger particles was observed, whereas cool season (November–April) precipitation events exhibited overall lower aerosol loading with an apparent influence from biomass burning particles. A significant relationship between aerosol optical properties and precipitation intensity was observed, which may be indicative of aerosol‐induced precipitation enhancement in each season, particularly during warm season non‐frontal precipitation.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Amplified fragment length polymorphism-based genetic diversity among cultivated and weedy rye (Secale cereale L.) accessions - T. Chikmawati; M. Miftahudin; B. Skovmand; J. Perry Gustafson (Genetic Resources and Crop Evolution, 2012)

Dodo remains from an in situ context from Mare aux Songes, Mauritius - Hanneke J. M. Meijer; Arike Gill; Perry G. B. de Louw; Lars W. Van Den Hoek Ostende; Julian P. Hume; Kenneth F. Rijsdijk (The Science of Nature, 2012)

Low-dimensional trade-offs fail to explain richness and structure in species-rich plant communities - Alexandra Esther; Jürgen Groeneveld; Neal J. Enright; Ben P. Miller; Byron B. Lamont; George L. W. Perry; Britta Tietjen; Florian Jeltsch (Theoretical Ecology, 2011)

Strategies for selection marker-free swine transgenesis using the Sleeping Beauty transposon system - Daniel F. Carlson; John R. Garbe; Wenfang Tan; Mike J. Martin; John R. Dobrinsky; Perry B. Hackett; Karl J. Clark; Scott C. Fahrenkrug (Transgenic Research, 2011)

Projected Reorganization of Florida Bay Seagrass Communities in Response to the Increased Freshwater Inflow of Everglades Restoration - Darrell Anthony Herbert; William B. Perry; Bernard J. Cosby; James W. Fourqurean (Estuaries and Coasts, 2011)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Seaglider observations of blooms and subsurface chlorophyll maxima off the Washington coast - M. J. Perry; B. S. Sackmann; C. C. Eriksen; C. M. Lee (Limnology and Oceanography, 2008)
From September 2003 to December 2007, autonomous, underwater Seaglider continuously ran a V‐shaped transect off Washington State from about 200‐m water depth (i.e., at the break between the shelf and slope) to offshore waters with depths >2700 m. Seaglider visited the offshore vertex at 47°N, 128°W, where our observations concentrated, approximately monthly. Seaglider measured temperature, conductivity, and dissolved oxygen to 1000 m and also recorded chlorophyll a (Chl a ) fluorescence and particulate optical backscatter to 150 m. Distinct interannual variation was documented in timing and depths of winter mixing, transition to a shallow summer pycnocline, and onset of mixed‐layer erosion in autumn. Chl a concentrations estimated from fluorescence were directly comparable among the seven laboratory‐calibrated sensors used, but their estimates exceeded concurrent, satellite‐derived concentrations by a factor of three. Seaglider optical profiles enabled interpretation of satellite imagery by revealing that the apparent autumn bloom after destratification was instead a vertical redistribution of phytoplankton from the subsurface maximum to a depth where they could be observed by satellites. Results of 4 yr of sampling within 25 km of the vertex demonstrate the value of gliders in ocean observing and their capability to carry out multiyear, fully autonomous operations under any sea state. The true power of glider programs will be realized in combination with other measurement platforms, including larger spatial coverage by satellites and more comprehensive biogeochemical measurements from moorings and occasional ship‐based sampling.

An extract of Salvia (sage) with anticholinesterase properties improves memory and attention in healthy older volunteers - Andrew B. Scholey; Nicola T. J. Tildesley; Clive G. Ballard; Keith A. Wesnes; Andrea Tasker; Elaine K. Perry; David O. Kennedy (Psychopharmacology, 2008)

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

First EFSA experiences with monitoring plans - Detlef Bartsch; A. Gathmann; S. Hartley; N. B. Hendriksen; R. Hails; K. Lheureux; J. Kiss; S. Mesdagh; G. Neemann; J. Perry; S. Renckens; J. Schiemann; et al. (Journal of Consumer Protection and Food Safety, 2007)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Fishing for Answers with Transposons - Shannon A. Wadman; Karl J. Clark; Perry B. Hackett (Marine Biotechnology, 2005)

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)

Proclivity and effectiveness in gall defence by soldiers in five species of gall-inducing thrips: benefits of morphological caste dimorphism in two species (Kladothrips intermedius and K. habrus) - S. P. Perry; T. W. Chapman; M. P. Schwarz; B. J. Crespi (Behavioral Ecology and Sociobiology, 2004)

Assessment of prey overlap between a native ( Polistes humilis ) and an introduced ( Vespula germanica ) social wasp using morphology and phylogenetic analyses of 16S rDNA - Marta L. Kasper; Andrew F. Reeson; Steven J. B. Cooper; Kym D. Perry; Andrew D. Austin (Molecular Ecology, 2004)
In newly invaded communities, interspecific competition is thought to play an important role in determining the success of the invader and its impact on the native community. In southern Australia, the native Polistes humilis was the predominant social wasp prior to the arrival of the exotic Vespula germanica (Hymenoptera: Vespidae) . Both species forage for similar resources (water, pulp, carbohydrate and protein prey), and concerns have arisen about potential competition between them. The aim of this study was to identify the protein foods that these wasps feed on. As many prey items are masticated by these wasps to the degree that they cannot be identified using conventional means, morphological identification was complemented by sequencing fragments of the mitochondrial 16S rRNA gene. GenBank searches using blast and phylogenetic analyses were used to identify prey items to at least order level. The results were used to construct complete prey inventories for the two species. These indicate that while P. humilis is restricted to feeding on lepidopteran larvae, V. germanica collects a variety of prey of invertebrate and vertebrate origin. Calculated values of prey overlap between the two species are used to discuss the implications of V. germanica impacting on P. humilis. Results obtained are compared to those gained by solely ‘conventional’ methods, and the advantages of using DNA‐based taxonomy in ecological studies are emphasized.

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

Resolving phytoplankton photoprotective : photosynthetic carotenoid ratios on fine scales using in situ spectral absorption measurements - Lisa B. Eisner; Michael S. Twardowski; Timothy J. Cowles; Mary Jane. Perry (Limnology and Oceanography, 2003)
Temporal changes in phytoplankton pigments and spectral absorption were evaluated during June 1998 in East Sound, Orcas Island, Washington. High‐resolution vertical profiles of in situ spectral absorption were obtained with a Wet Labs ac‐9 (nine‐wavelength absorption and beam attenuation meter), and pigment concentrations were determined for discrete water samples using high‐performance liquid chromatography (HPLC). Fucoxanthin was the most abundant carotenoid, indicating the dominance of diatoms. We computed a slope index to evaluate changes in shapes of the in situ particulate absorption coefficient ( a p ) spectra, a p slope = ( a p 488 − a p 532)/( a p 676(488 − 532 nm)). A clear linear relationship was seen between ratios of photoprotective : photosynthetic carotenoids (PPC : PSC) and these a p slopes. While pigment package effects may alter the absorption spectra, in our data set we still found a significant relationship between pigment ratios and in situ a p slopes. Retrieval of this relationship was facilitated by the low and relatively constant detrital absorption coefficient ( a d ) values in our study area. Similar relationships were found between PPC:PSC ratios and the estimated phytoplankton absorption coefficient ( a ph ) spectra. High PPC:PSC ratios and steeper a p slopes were associated with high‐light levels. Our results suggest that in situ absorption measurements can be used to estimate PPC:PSC ratios in areas where the ad contribution is low or can be estimated. These variations in pigment ratios and spectral absorption reflect photoacclimation responses and/or changes in phytoplankton species composition and suggest in situ absorption measurements may be used to estimate pigmentation changes over fine temporal and spatial scales.

The effect of leg flexion angle on the mechanomyographic responses to isometric muscle actions - Kyle T. Ebersole; Terry J. Housh; Glen O. Johnson; Tammy K. Evetovich; Douglas B. Smith; Sharon R. Perry (European Journal of Applied Physiology, 1998)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Lipids of the marine bacterium Flexibacter polymorphus - R. B. Johns; G. J. Perry (Archives of Microbiology, 1977)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)